2014
DOI: 10.1021/jp410805q
|View full text |Cite
|
Sign up to set email alerts
|

Melting Behavior of Aluminum Nanowires in Carbon Nanotubes

Abstract: Molecular dynamics simulation has been performed to study melting behavior of aluminum nanowires (NWs) encapsulated in armchair single-walled carbon nanotubes (SWCNTs). Results show that intriguing phenomena may appear when the diameters of the inner NWs exceed a threshold value that melting occurs first at the inner layers, followed by the diffusion of the inner atoms toward the surface layers. Two melting temperatures can be obtained while the first one is even lower than that of the free-standing one in som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…715,721 It has been clearly demonstrated that these structural changes of confined species has a direct impact on the properties of the NP. The thermal stability of Al, 722 Au, [723][724][725] Au-Pt, 726 Cu, 727,728 Pd, 729 Pd-Pt, 730 Pd-Au-Pt, 731 PtCo, 732 PtCu, 733 or Pt 734 clusters located in the inner cavity of CNT or carbon nanospheres has been studied by MD calculations. In the case of gold, the melting phenomenon starts from the innermost layer, when the freezing one begins from the outermost layer for confined NP.…”
Section: Electronic or "Hard" Effectsmentioning
confidence: 99%
“…715,721 It has been clearly demonstrated that these structural changes of confined species has a direct impact on the properties of the NP. The thermal stability of Al, 722 Au, [723][724][725] Au-Pt, 726 Cu, 727,728 Pd, 729 Pd-Pt, 730 Pd-Au-Pt, 731 PtCo, 732 PtCu, 733 or Pt 734 clusters located in the inner cavity of CNT or carbon nanospheres has been studied by MD calculations. In the case of gold, the melting phenomenon starts from the innermost layer, when the freezing one begins from the outermost layer for confined NP.…”
Section: Electronic or "Hard" Effectsmentioning
confidence: 99%
“…41 The C-C interaction is modeled by an adaptive intermolecular reactive empirical bond order (AIREBO) potential. 42,43 Due to the fact that metal and carbon can only form so bonds via charge transfer from the p electrons in the sp 2 hybridized carbon to the empty 4s states of metal, 44 the 12-6 Lennard-Jones (L-J) potential is utilized to describe the metal-substrate interactions with the following parameters: 3 C-Al ¼ 0.0309 eV, s C-Al ¼ 3.422Å, 45 3 C-Pb ¼ 0.01751 eV, and s C-Pb ¼ 3.288Å. [46][47][48][49] The perpendicular of the substrate is considered as the z-direction.…”
Section: Models and Methodsmentioning
confidence: 99%
“…The C-C interaction is modeled by an adaptive intermolecular reactive empirical bond order (AIREBO) potential 37 . Because metal and carbon can only form soft bonds via charge transfer from the π electrons in the sp 2 hybridized carbon to the empty 4 s states of metal 38 , we utilized the 12-6 Lennard-Jones (L-J) potential with a well depth ε = 0.0309 eV and size parameter σ = 3.422 Å to describe the Al-C interactions 39 , and a well depth ε = 0.01751 eV and size parameter σ = 3.288 Å was determined by Lorentz-Berthelot combining rules 40 41 to calculate the Pb-C interactions 42 . With these parameters, we calculated the equilibrium contact angle as 83.43° for Al and 112.12° for Pb on the flat graphene at 1500 K, which accord well with the experimentally measured contact angle of Al (about 85°) 29 and Pb (about 110°) 43 .…”
Section: Methodsmentioning
confidence: 99%